2007
DOI: 10.1111/j.1572-0241.2007.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Serum Levels Are Elevated in Patients With Liver Cirrhosis and Hepatocellular Carcinoma

Abstract: Serum angiopoietin-2 levels are elevated in patients with cirrhosis, implicating a possible role of the angiopoietin-Tie-2 system for neoangiogenesis in cirrhosis. Serum levels are further elevated in patients with HCC, suggesting the potential use of angiopoietin-2 as a marker for the detection of cirrhosis and HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 42 publications
8
43
1
Order By: Relevance
“…Given the limited value of CgA in this subgroup of patients, Ang-2 might prove useful for tumor follow-up under these conditions. Similar observations of potential prognostic use of Ang-2 have been reported in selected tumor entities such as hepatocellular carcinoma (19), melanoma (15), or lung cancer (20), although elevated serum levels are not necessarily prognostic indicators (12). Taken together, our clinical and experimental data strongly link Ang-2 to disease progression of neuroendocrine tumors.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Given the limited value of CgA in this subgroup of patients, Ang-2 might prove useful for tumor follow-up under these conditions. Similar observations of potential prognostic use of Ang-2 have been reported in selected tumor entities such as hepatocellular carcinoma (19), melanoma (15), or lung cancer (20), although elevated serum levels are not necessarily prognostic indicators (12). Taken together, our clinical and experimental data strongly link Ang-2 to disease progression of neuroendocrine tumors.…”
Section: Discussionsupporting
confidence: 68%
“…digoxigenin-UTP-labeled sense and antisense RNA-probes were generated by in vitro transcription (DIG-RNA Labeling Kit, Roche) of a 1,519-bp human Ang-2 cDNA fragment subcloned into the pBluescript II SK vector. The in situ hybridization procedure was done as previously described (19). A grading system for semiquantitative evaluation of Ang-2 mRNA expression was applied (grade 0, ≤5% of epithelial cells; grade 1, 5-25%; grade 2, 25-75%; grade 3, ≥75%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of VEGF A, ANGPT2 potentiates the maturational activity of ANGPT1 on neovessels, whereas in its absence, ANGPT2 competes with ANGPT1, thus promoting vascular regression (26,27). Additionally, the interaction between ANGPT2 and VEGF plays a role in both liver fibrosis (28) and hepatocellular carcinoma (29). Our findings on the additive effect of ANGPT1 and ANGPT2 on MT in patients with BA may be explained by the fact that VEGF A is strongly expressed in portal structures, including the medial layer of hepatic artery branches in these patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…Because of a paucity of antibodies to Ang2 that allow robust immunohistochemistry, very few studies have documented the levels or location of Ang2 protein in diseased human tissue. However, several in situ hybridization studies have revealed increased levels of Ang2 expression in cancers of different origin, including neuroendocrine tumors (Detjen et al 2010), hepatocellular cancer (Chen et al 2001;Scholz et al 2007), gastric cancer (Moon et al 2006), angiosarcoma (Brown et al 2000), carcinosarcoma (Emoto et al 2004), and astrocytoma (Zagzag et al 1999). Interestingly, some studies report increased expression of Ang2 in both endothelial cells and tumor cells (e.g., Helfrich et al 2009;Detjen et al 2010), whereas other studies have shown Ang2 expression limited to the vasculature and not in tumor cells (Stratmann et al 1998;Zagzag et al 1999;Moon et al 2006;Goede et al 2010).…”
Section: Expression Of Ang2 Is Increased In Several Disease Settingsmentioning
confidence: 99%